Strategy for Developing Civic Education Based on Character to Improve Students’ Social Morality - Sofiani, Mutia (International Journal of Students Education, 2024)
Civic Education (PKn) plays an important role in shaping students’ social morality through character values. Character-based Civics development strategies aim to instill values such as honesty, responsibility, tolerance, and social care. This study examines the implementation of Civics development strategies that focus on participatory learning, contextual approaches, and the instillation of moral values through real-life experiences. Moral degradation in Indonesia, which includes issues such as lack of honesty, justice, and ethics, shows the need to instill moral values from an early age. Civic education not only serves to provide knowledge about the rights and obligations of citizens, but also to shape the character of students to have good and responsible behavior. The results show that a character-based approach can enhance students’ social awareness, strengthen relationships among students, and reduce negative behaviors. This strategy also involves collaboration between teachers, parents, and the community to create an environment that supports moral education. Thus, character- based education in Civics can be a solution to strengthen social morality among students, preparing them to be responsible and ethical citizens.